MENGENAL SUHU PERMUKAAN LAUT DARI PENGINDERAAN JAUH - Marindah Yulia Iswari (OSEANA, 2017)
IDENTIFYING SEA SURFACE TEMPERATURE THROUGH REMOTE SENSING. Sea surface temperature is one of the physical parameters of oceanography that is useful to determine the water quality. Sea surface temperature can be observed using remote sensing technology. Remote sensing sensors must have a thermal infrared or a passive microwave to identify sea surface temperature. NASA's Ocean Color Web has provided sea surface temperature data processed by NASA's Ocean Biology Processing Group (OBPG) team. MODIS and VIIRS are remote sensing instruments used for sea surface temperature data on NASA's Ocean Color Web. The SST data provided in the form of data level 2 and level 3 are processed in daily, weekly, monthly and even yearly.